Optimizing Picture Series to Enhance Writing Skills of Senior High School Students - Raharjo, Priyo (Universitas Muhammadiyah Gresik, 2018)
This paper is aimed to improve writing skill of senior high schools students by using picture series technique. To achieve the objective, this paper focuses on 3 (three) previous studies about teaching writing using picture series. Those studies are taken from some English thesis and journal about picture series. After compiling and understanding all the findings of those research, the conclusion is given based the usage of picture series in several written form and also the effectiveness of techniques by using pictures series during the process of students writing activities. The discussion told that the improving of students writing skills using picture series, mostly the previous researcher uses pre-test and post-test as data collection. The result of post-test writing is always higher or better than pre-test after using picture series technique. Most of previous researchers use quantitative research method because the result of the research can be measured accurately. The application of picture series can be improved in the written form of narrative text, descriptive text, and recount text. The usage of picture series is expected to improve the students’ writing ability as it can help them with the new ideas and vocabularies. Implementing picture series is also effective to improve the students’ motivation in the writing process. The common writing problems in the aspects of content, vocabulary, language use and organization also can be reduced by implementing picture series in the teaching and learning process of writing